Reabilitação estética com lentes de contato em paciente com desgaste dentário extrínseco - Lima, Karoline Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
Currently, the systems used for aesthetic rehabilitation in anterior areas in an indirect way have reached a level of excellence in the aesthetic and resistance requirements that may have their indication extrapolated in cases of parafunction and / or extrinsic and intrinsic factors of tooth wear. The main intrinsic factor, that leads to tooth wear, is patients with gastroesophageal reflux, whereas, the extrinsic factors due abusive use of acidic substances, such as citrus fruits and acidulated drinks play a role on dental loss. Thus, those factors combined with very abrasive pastes and excessive use of force in the brushing, that can be aggravated by the use of not extra soft brushes, normally present chronic problem resulting in loss of dental structures that will bring about aesthetic and functional damages. Therefore, this study aims to describe a clinical case of patient with loss of tooth structure associated to the mentioned etiological factors above, rehabilitated with facets and contact lenses with the e-max (Lithium Dissilicate) system

Os sistemas utilizados atualmente para reabilitação estética em áreas anteriores de maneira indireta alcançaram um nível de excelência nos quesitos estética e resistência que podem ter sua indicação extrapoladas em casos de parafunção e/ou fatores extrínsecos e intrínsecos de desgastes dentários. O principal fator intrínseco são pacientes portadores de refluxo gastroesofágico. Dentre os fatores extrínsecos temos como principal representante o uso abusivo de substâncias ácidas, como frutas cítricas e bebidas aciduladas. Associado a uma escovação com pastas muito abrasivas e com o uso excessivo de força na escovação que podem ser agravadas com o uso de escovas que não sejam extra macias, temos como resultado crônico, a perda de estruturas dentárias que trarão prejuízos estéticos e funcionais. Esse trabalho tem por objetivo descrever um caso clínico de paciente com perda de estrutura dentária frente aos fatores etiológicos citados, reabilitado com facetas e lentes de contato com o sistema e-max (Dissilicato de Lítio)
Keywords: Estética dentária; Desgaste dos dentes; Porcelana dentária; Facetas dentárias; Esthetics, Dental